Letters and diaries of Kathleen Ferrier - Ferrier, Kathleen 1912-1953 (Boydell Press, 2023)
Until now, Kathleen Ferrier has been a glorious voice, but through the pages of these fascinating letters and diaries, never previously published, we get to the real person
Title from publisher's bibliographic system (viewed on 21 Mar 2023)
Keywords: Ferrier, Kathleen / 1912-1953 / Correspondence; Ferrier, Kathleen / 1912-1953 / Diaries; Ferrier, Kathleen -- 1912-1953; Contraltos / England / Correspondence; Contraltos / England / Diaries; Tagebuch -- 1942-1953; Briefsammlung -- 1940-1953